2011
DOI: 10.1002/poc.1896
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the smiles rearrangement in the activation mechanism of proton pump inhibitors

Abstract: This work describes the conformational behavior and the activation mechanism of timoprazole and substituted prazoles from the most stable conformation to the sulphenic acid. The stability of the conformers can be explained by the presence of hydrogen bonds, stereoelectronic effect because of the lone pair of sulfur atom and the N … C and N … S interactions. The first step of the Smile rearrangement is a nucleophilic addition to benzimidazole by pyridine moiety, which depends on the difference of the electron p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
4
Order By: Relevance
“…The structures and monoisotopical masses of adducts were determined by considering the different mechanisms of omeprazole action previously reported (Fig. 1 ) 22 24 , 26 . Moreover, since the derivatized Cys residues did not recover after the treatment with DTT, we assumed that all identified adducts were attached through covalent bonds that do not involve disulfide bridges.…”
Section: Resultsmentioning
confidence: 99%
“…The structures and monoisotopical masses of adducts were determined by considering the different mechanisms of omeprazole action previously reported (Fig. 1 ) 22 24 , 26 . Moreover, since the derivatized Cys residues did not recover after the treatment with DTT, we assumed that all identified adducts were attached through covalent bonds that do not involve disulfide bridges.…”
Section: Resultsmentioning
confidence: 99%
“…Ein starker primärer kinetischer 16 Die Substitutionsschritte in Claydens Arbeiten sind Beispiele fürT ruce-Smiles-Umlagerungen, [84] d. h. intramolekulare Substitutionsreaktionen von Kohlenstoff-Nukleophilen und Stickstoff-Abgangsgruppen, die über einen spiro-Übergangszustand oder ein spiro-Intermediat ablaufen. Ein ganz anderes Beispiel fürd ie cS N Ar-Chemie wurde von Coquerel et al [85] 2013 beschrieben, welches einen einer Smiles-Umla- [89] 275 [90] und 278 [91] wurden mithilfe von…”
Section: Aufsätzeunclassified
“…Aufsätze quantenchemischen Modellen [89][90][91][92] untersucht (Schema 38), und jedes davon ergab klare Intermediate anstelle von konzertierten ipso-Substitutionen. Insgesamt zeigen die Studien zu Smiles-Umlagerungen, dass zwischen konzertierten und schrittweisen Substitutionsreaktionen ein feines Gleichgewicht besteht.…”
Section: Angewandte Chemieunclassified
“…The free energy profile suggests that the formation of Timo-BzH + could be barrierless, where Timo-BzH + and Timo-TS1 are energetically higher by 0.4 kcal/mol than timoprazole, however, electronic energy ( Δ E aq ) results show that Timo-BzH + is stable by 1.4 kcal/mol compared to Timo-TS1 (Table S2). On the other hand, there are reports available in the literature, which suggests that the protonation of the Bz moiety might be favorable compared to the Py unit. , Therefore, we have examined the p K a of both Bz and Py rings using the M062X/6-31++G­(d,p) level of theory. The calculated p K a values suggest that the N1 nitrogen of the Py moiety is more basic than the N3 nitrogen of the Bz unit which is in agreement with the experimental report of Shin et al (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetics and pharmacodynamics studies have revealed that the S -isomer of the proton pump inhibitors are more superior compared to the R- isomers. , Like the drug omeprazole, other irreversible proton pump inhibitors, e.g., timoprazole, tenatoprazole, rabeprazole, pantoprazole, and lansoprazole, are racemates in nature . It is important to note that omeprazole and other proton-pump inhibitors are prodrugs which are converted to their active form in acidic environments of the parietal cell. Proton pump inhibitors are weak bases and generally concentrate in the acidic secretory canaliculi of the parietal cell, where they are activated to an acid-activated complex by a proton-catalyzed process (Scheme ) . The acid-activated complex makes covalent bond with the sulfydryl groups of cysteine-813 or -822 residues in the extracellular domain of the H + ,K + -ATPase to generate stable disulfide complex and thereby inhibiting the enzyme activity.…”
Section: Introductionmentioning
confidence: 99%